SYMBOLIC REALITY CONSTRUCTION OF THE K-POP COMMUNITY ON TWITTER - Astari, Devi Wening; Agustina, Dwi Pela; Nurussa’adah, Erfina (Master of Communication Science Program, Universitas Diponegoro, 2024)
This research aimed to find a model of symbolic interaction in the BTS fanbase through exchanging fantasy-themed messages that create group awareness and produce feelings of togetherness. The research was conducted using qualitative methods and virtual ethnographic procedures. The research subject was a fanbase account that actively provided various information on Twitter that led to the dramatization of BTS content. The data was obtained through community members' observations through Focus Group Discussions with ARMY. The criteria for selecting informants were 1) fans who actively upload and interact with BTS; 2) actively followed accounts that ARMY follows with at least 50,000 followers; 3) followed accounts get a lot of interactions, comments, retweets, or quote retweets; 4) the selected ARMY had a Twitter account that has followed the selected account and has contact with that account. The results showed that the development of the ARMY community on Twitter was based on constructing a shared symbolic reality. The forms were a visual video, photo, word game, or a combination. ARMY utilized fantasy themes to interact with fellow ARMY to build closeness and a strong sense of family by implementing a culture of active participation in the community. This research also provided an overview of ARMY's symbolic reality construction model on Twitter and the relationship between cultural participation theory and the symbolic interactions of K-pop fans.